2017
DOI: 10.3389/fpsyg.2017.00574
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling Working Memory Functioning in Mood States of Bipolar Disorder: A Systematic Review

Abstract: Working memory (WM) deficits are often reported in patients with Bipolar Disorder (BD). However, it is not clear about the nature of these WM deficits (update or serial order processes) and their association with each BD states (euthymic, mania, and depressive). This review investigated the association between BD patient's states and the functioning of WM components. For this purpose, we carried out a systematic review fulfilling a search in the databases Medline, Scopus, SciELO, and Web of Science using speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 99 publications
(417 reference statements)
1
11
0
1
Order By: Relevance
“…All remaining effect sizes were classified as medium. The analysis of composite scores within each domain revealed that effect sizes were numerically larger for verbal than visual measures of both working memory and episodic memory, corroborating previous findings in the literature (11,13). However, heterogeneity was also larger for verbal memory instruments than those measuring visual memory.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…All remaining effect sizes were classified as medium. The analysis of composite scores within each domain revealed that effect sizes were numerically larger for verbal than visual measures of both working memory and episodic memory, corroborating previous findings in the literature (11,13). However, heterogeneity was also larger for verbal memory instruments than those measuring visual memory.…”
Section: Discussionsupporting
confidence: 85%
“…The effect including the outlier was calculated at g = 0.54 (95% CI: 0.34-0.74). 13 One outlier removed. The effect including the outlier was calculated at g = 0.58 (95% CI: 0.25-0.91).…”
Section: Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the significant deficits in working and verbal memory suggest an impact on frontal lobe functioning, disruption of frontal–subcortical or mesolimbic circuitry, or partial executive dysfunction (Ferrier et al., 1999). Soraggi‐Frez, Santos, Albuquerque, and Malloy‐Diniz (2017) carried out a comprehensive review and suggested that working memory deficit is more likely to be state‐independent in BD, indicating that mood episodes are associated with working memory impairment (Soraggi‐Frez et al., 2017). Working memory is sometimes referred to be part of executive function and has been reported to be impaired in BD patients as well as in AD patients (Soraggi‐Frez et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Anterior cingulate cortex (ACC) and orbitofrontal cortex (OFC) in the PFC, known to be involved in the cognitive and emotional control, are among the investigated regions of BD deficits. In fact, BD patients have shown deficits in the ACC and OFC regions from brain structural, functional, neuropathological and as inferred indirectly from neuropsychological studies . Altered connectivity with the ACC and OFC regions has been reported sporadically in BD at rest or during challenge tasks .…”
Section: Introductionmentioning
confidence: 99%